Tren Fotografi Pre-Wedding dalam Perspektif Mazhab Syafi’i tentang Aurat dan Ikhtilāṭ - Muhammad Ma’ruf; Khoirul Anwar (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the trend of pre-wedding photography from the perspective of Imam Shafi'i's thoughts on the concepts of aurat and ikhtilāṭ, and to examine its implementation in the social context of Jombang through a multi-case study approach. The research method used was a qualitative multi-case study design, involving several prospective brides and grooms, photographers, religious leaders, and the Office of Religious Affairs (KUA) as research subjects. Data collection techniques were conducted through observation, in-depth interviews, and documentation, while data analysis utilized the interactive model of Miles and Huberman. The results of this study indicate that pre-wedding photography practices in Jombang Regency vary, ranging from those that are relatively compliant with sharia principles to those that potentially violate the provisions of aurat and ikhtilāṭ according to the Shafi'i school of thought. Dominant factors influencing these practices include the influence of popular culture, social media, religious understanding, and aesthetic and economic considerations. This study emphasizes the importance of strengthening marital fiqh literacy and Islamic visual ethics so that the tradition of pre-wedding photography can be adapted to sharia values ​​without neglecting the social and cultural aspects of society.